Copper Winding Tool Design Using Ergonomic Function Deployment and Design for Manufacturing and Assembly: Desain Alat Penggulung Tembaga Menggunakan Penyebaran Fungsi dan Desain yang Ergonomis untuk Manufaktur dan Perakitan - Islamsyah, M Habibie Nur; Tranggono, Tranggono (Indonesian Journal of Innovation Studies, 2025)
General Background: Rewinding electric motors is a fundamental aspect of electric motor maintenance, especially involving copper coil winding. Specific Background: Manual winding tools currently used in workshops are often inefficient, imprecise, and unsuitable for large wire diameters. Knowledge Gap: Despite the central role of coil winding, ergonomic and production-efficient tools for this process remain limited in design and functionality. Aims: This study aims to develop a more ergonomic and efficient copper winding tool using Ergonomic Function Deployment (EFD) and Design for Manufacturing and Assembly (DFMA) methodologies. Results: Testing revealed that the newly designed tool significantly improves winding speed—tripling productivity from 1 to 3 coil blocks per minute—while also reducing process recalculations, balancing workloads, and enhancing operator comfort and safety. Novelty: Unlike existing tools, the proposed solution incorporates user-centered ergonomic design with optimized manufacturability and assembly, addressing both usability and production constraints. Implications: This innovation can increase workshop productivity, improve customer satisfaction, and serve as a model for future ergonomic tooling in motor rewinding operations. Highlights: Increases coil winding speed by 3×. Enhances operator comfort and safety. Reduces recalculation and production errors. Keywords: Copper Winding Tool, Electric Motor Rewinding, Ergonomic Design, DFMA, Workshop Efficiency